ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLIBATAN INDIVIDU DALAM PEMILIHAN PAKAIAN - Isitiharini . (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
Many modern societies are characterised by a strongly held belief that to have is to be. Thus, individuals often definethemselves and others in terms of their possessions. Possessions have come to serve askey symbols for personal qualities, attachments and interest. A possession that holds a significant position in society is fashionclothing. Fashion clothing has been described as possessing something approximatinga code. This study explores the relationship between consumers gender, age, level of materialism, and fashion clothing involvement. Data were gathered via a self-completed survey in Bandung, resulting in 478 responses being returned. The results indicate that fashion clothing involvement is significantly effected by a consumer’s degree of materialism, gender and age.